Floating protective barriers: Evaluation of seaworthiness through physical testing, numerical simulations and field deployment. (1st May 2021) - Knysh, Alexander; Coyle, Jackson; DeCew, Judson; Drach, Andrew; Swift, M. Robinson; Tsukrov, Igor
Abstract: Floating protective barriers provide essential protection to critical governmental, commercial, and private assets that are vulnerable to water-borne intrusion, such as liquefied natural gas terminals, tankers, etc. These barriers require additional evaluation in the case of their deployment at significant water depth in offshore environments. The seaworthiness of the Triton® barrier design developed by HALO Maritime Defense Systems (US) was investigated through a combination of field deployment, physical testing and numerical simulations. The full-scale Triton® barrier, deployed and inspected south-southwest of White Island, Isles of Shoals, New Hampshire, provided important information on its dynamic behavior and the overall structural integrity under monitored environmental conditions. Physical tests of a Froude-scaled barrier model were conducted in Chase Ocean Engineering Laboratory wave tank at the University of New Hampshire to properly measure response of the structure and its mooring to different single-frequency waves directed parallel and normal to the model. Both physical tests and field study load cases were numerically simulated in finite element Hydro-FE software. The comparisons indicated a good correspondence between physical tests and numerical models in terms of heave, pitch, roll and force response amplitude operators. Overall, the full-scale Triton® barrier has demonstrated robust performance during the offshore field deployment. Highlights: Seaworthiness of a protective barrier is investigated through physical testing, numerical simulations and field deployment. The full-scale barrier was deployed, inspected and monitored near the of White Island, Isles of Shoals, New Hampshire, USA. Physical tests of a Froude-scaled barrier model were conducted in a wave tank at the University of New Hampshire. Both physical tests and field study load cases were numerically simulated in finite element Hydro-FE software. Field, physical and numerical tests are compared in terms of heave, pitch, roll and force response amplitude operators.